Avaliação e modelização da dinâmica de carbono e nitrogênio em solo com o uso de dejetos de suínos - Giacomini, Sandro José (2005)
The managedment of the pig manure, in the slurry or solid form (deep bedding), and how it is applied to the soil, in the surface or incorporated, must affect the dynamics of the C and the N in the soil. The objectives of this work were: 1) to evaluate the dynamics of the C and the N in soil and to evaluate the N supply to maize which were applied pig manure in the slurry and solid form, in no-tillage and minimum tillage system; and 2) to use the STICS model (BRISSON et al., 1998) to simulate the dynamics of N and water in the soil-plant system with the use of pig slurry in maize under no-tillage system. To reach the first objective, three experiments were realized. Two of them in the field conditions, during the period of 2002/03 in the Experimental Area of the UFSM/RS Soil Department in a typic Hapludult and one of them in laboratory conditions. The treatments consisted in the application or no application of pig manure in the slurry and solid form (deep bedding) on the crop oats residues with and without incorporation to the soil in the maize. Aiming to reach the second objective, a data set generated in the Experimental Area of the UFSM Soil Department during the period of 1998 to 2002, involving the N dynamics in the soil-plant system, with the use of pig slurry in notillage system was used. The gotten results had indicated that the N losses by NH3 volatilization were higher with the application of pig slurry than with the application of solid manure and that these losses decrease with the incorporation of the manure to the soil. The amounts of mineral N in the soil layer of 0-90 cm did not differ between the treatments with and without incorporation of the manure in spite of the lost N amount by volatilization has been higher in the treatment without incorporation. The incorporation of the manure to the soil did not increase the straw C decomposition and nor the N immobilization. The presence of the oats straw stimulated the immobilization of the ammoniacal N applied with the pig slurry. The solid manure presented low nitrogenous fertilizing otential to the maize when compared to the pig slurry in terms of the low mineralization rate of the organic N, present in the deep bedding. The N-N2O emission increased with the application of the pig slurry on the oats straw in relation to the system with straw and without pig slurry. The pig slurry ammoniacal 15N recovery by the maize in physiological maturation stage was only 14.9%. In the same period, only 49.2% of the ammoniacal 15N applied with the slurry pig slurry were recuperated in the soil and the plant (aerial part + roots), indicating that more than a half of the ammoniacal N applied with the pig slurry was lost through the volatilization, lixiviation and denitrification processes. The STICS model underestimates the amount of N lost by ammonia volatilization after the pig slurry application. The use of a factor in STICS to express the N losses by ammonia volatilization provided an improvement in the simulations of the N dynamics in the soil. The water dynamics in the soil layer of 0 - 60 cm was simulated by STICS with an error lower than 13.5%. These work results showed that the STICS reparametred model presents potential to be used in subtropical weather conditions in the simulation of the N and water dynamics in no-tillage system with the use of pig manure.